Individualized Corneal Patching for Treatment of Corneal Trauma Combined with Tissue Defects - Ting Zhang; Yanni Jia; Suxia Li; Weiyun Shi (Journal of Ophthalmology)
Aim. To evaluate the efficacy of individualized corneal patching using a minimal graft for corneal trauma combined with tissue defects. Methods. Fifteen eyes (15 patients) were enrolled in this study, including 8 eyes with corneal perforation induced by removal of metal foreign bodies, 5 eyes with corneal laceration resulting from metal trauma, and 2 eyes with pencil injuries to the cornea. The size, shape, and depth of the tissue defects were assessed. For corneal perforation or irregular tissue defects, if the diameter or length was ≥3.0 mm, traditional penetrating keratoplasty (PK) or lamellar keratoplasty (LK) was adopted; if the diameter or length was ＜3.0 mm, a conical or irregular patch consistent with the defects was used. The visual acuity, corneal status, and postoperative complications were observed during the follow-up. Results. The diameter of corneal perforations was 1.0 mm in 2 eyes, 1.5 mm in 1 eye, 2.0 mm in 4 eyes, and 3.5 mm in 1 eye. During their PK procedures, a conical corneal graft was used in 7 eyes, while a traditional cylindrical graft was used in 1 eye. The other 7 eyes had corneal trauma combined with irregular tissue defects, which were full-thickness corneal defects in 5 eyes and lamellar defects in 2 eyes, all less than 3.0 mm in length. Thus, five eyes received PK, and 2 eyes received LK using an irregular wedge-shaped patch. The visual acuity increased greatly postoperatively, with mild corneal astigmatism. None of the patients developed immune rejection. Conclusion. Individualized corneal patching with a minimal graft can save corneal materials, relieve corneal scars, gain a good visual prognosis, and avoid immune rejection in the treatment of corneal trauma combined with tissue defects.